HIV infection and the risk of diabetes mellitus. - Butt, Adeel A; McGinnis, Kathleen; Rodriguez-Barradas, Maria C; Crystal, Stephen; Simberkoff, Michael; Goetz, Matthew Bidwell; Leaf, David; Justice, Amy C (AIDS (London, England), 2009)
The influence of HIV infection on the risk of diabetes is unclear. We determined the association and predictors of prevalent diabetes mellitus in HIV infected and uninfected veterans.
Keywords: Adult; Age Factors; Aged; Anti-HIV Agents; Body Mass Index; Diabetes Mellitus, Type 2; Epidemiologic Methods; Female; Hepatitis C, Chronic; HIV Infections; HIV-1; Humans; Male; Middle Aged; Sex Factors; United States